2022
DOI: 10.1002/cbic.202200168
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Gene Expression Knock‐Down by Chemically and Structurally Modified Gapmer Antisense Oligonucleotides

Abstract: We analyzed the effect of modified nucleotides within gapmer antisense oligonucleotides on RNase H mediated gene silencing. Additionally, short hairpins were introduced into antisense oligonucleotides as structural motifs, and their influence on biological and physicochemical properties of pre-structured gapmers was investigated for the first time. The results indicate that two LNA residues in specified positions of the gap flanking regions are sufficient and favorable for efficient knock-down of the β-actin g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 26 publications
(61 reference statements)
0
2
0
Order By: Relevance
“…In a recent study that used PS-modified gapmers flanked with LNA-modified residues, the addition of a small (3 bp) or medium (5 bp) double-stranded stem to the 3'-end of the gapmer resulted in a more active oligonucleotide, while the addition of a 7 bp stem did not improve activity. [53] When the same length stems were added on the 5'-end the ASO with the 5 bp stem was the least active, which implies that the local context of the secondary structure also matters. The authors hypothesized that the increasing efficiency of the oligos with the hairpin structure was a result of higher stability against exonucleases, which is especially relevant for gapmers which have unmodified residues.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a recent study that used PS-modified gapmers flanked with LNA-modified residues, the addition of a small (3 bp) or medium (5 bp) double-stranded stem to the 3'-end of the gapmer resulted in a more active oligonucleotide, while the addition of a 7 bp stem did not improve activity. [53] When the same length stems were added on the 5'-end the ASO with the 5 bp stem was the least active, which implies that the local context of the secondary structure also matters. The authors hypothesized that the increasing efficiency of the oligos with the hairpin structure was a result of higher stability against exonucleases, which is especially relevant for gapmers which have unmodified residues.…”
Section: Discussionmentioning
confidence: 99%
“…There is some prior work that suggested that secondary structure formation can affect ASO activity. In a recent study that used PS‐modified gapmers flanked with LNA‐modified residues, the addition of a small (3 bp) or medium (5 bp) double‐stranded stem to the 3′‐end of the gapmer resulted in a more active oligonucleotide, while the addition of a 7 bp stem did not improve activity [53] . When the same length stems were added on the 5′‐end the ASO with the 5 bp stem was the least active, which implies that the local context of the secondary structure also matters.…”
Section: Discussionmentioning
confidence: 99%